STATUS KEBERSIHAN RONGGA MULUT DAN KEBUTUHAN PERAWATAN JARINGAN PERIODONTAL PADA LANSIA DI DAERAH PESISIR PUGER, KABUPATEN JEMBER - Utha, Maria Fransisca; Fany, Manta; Wahyukundari, Melok Aris; Pudjiastuti, Peni; Prasetya, Rendra C.; Harmono, Happy; Wanodyo, Ari Tri; Sari, Desi Sandra (Jurnal Kesehatan, 2024)
Background: Periodontal disease is a dental and oral health problem that is often experienced by the elderly. Aging affects the ability of the elderly to carry out their daily activities, including cleaning the oral cavity. Increased accumulation of calculus due to poor oral hygiene can lead to the incidence of periodontal disease which affects the quality of life of the elderly. Purpose: to examine the status of oral hygiene and the need for periodontal tissue care in the elderly in the Pesisir Puger and Payangan area, Jember Regency. Methods: Descriptive observational with a cross-sectional approach. Subjects were selected as many as 192 elderly by purposive sampling technique. Data were obtained by taking questionnaires and clinical examinations in the form of OHI-S and CPITN. Results: the majority of elderly in the Pesisir Puger area of Jember district have a poor oral hygiene status of 96.88% and , the condition of the periodontal tissue has a 4-5 mm periodontal pocket of 66.67% and the need for periodontal tissue treatment is in the form of oral hygiene instructions and SRP procedures of 96.88%. Conclusion: Majority of the elderly in Pesisir Puger and Payangan have poor oral hygiene and require periodontal tissue treatment in the form of oral hygiene instructions and scaling and root planing procedures